Rhetorical Unconsciousness, Productive Discursive Repression, and Political Psychoanalysis - Bruner, Michael Lane (ALBAHITH ALALAMI, 2024)
The history of rhetorical practice has been a history of intentional persuasion, but philosophers and psychologists for centuries have argued, and persuasively so, that much of human subjectivity, and thus much of human persuasion, has profound unconscious dimensions that lead to forms of personal and political pathology. To better understand the roots of these pathologies, which lead to madness, violence and war, this essay explores rhetorical unconsciousness in ways that go far beyond simple notions such as “subliminal advertising,” or the conscious manipulation of unconsciousness, to explain how our very languages and the vast majority of beliefs derived from them are normally unconscious. To accomplish this task, I first engage in a general discussion of rhetorical unconsciousness, then summarize a conceptual framework for identifying different aspects of the same (i.e., the unsayable, the unspoken, and the unspeakable), concluding with a brief discussion of how the analysis of unspeakable things can serve as the basis for a new form of political psychoanalysis.